Gynecological Issues among Women Receiving M.D.R. Treatment for Tuberculosis - Bibi Sajida, Zainab Zubair, Ramsha Depar, Iram Yousaf, Sheh Bibi, Nargis Gulab (Pakistan Journal of Medical & Health Sciences, 2023)
Background: MDR-TB (multidrug resistant tuberculosis) is becoming a global concern, particularly in developing countries. Most clinical approaches emphasize infection control and managing drug-resistance. Moreover, little focus is placed on the reproductive health problems that women suffer from. In this research, efforts are made to assess the prevalence and pattern of gynecological problems among women undergoing treatment for MDR-TB. Methods: From May 2021 to June 2023, a descriptive cross-sectional study was conducted at Gynae and Obs department of DHQ hospital KDA. The study sample consisted of 59 women between the ages of 15-49 who were on MDR-TB therapy for a minimum of three months. Information pertaining to classifiable abnormalities of menstruation, inflammatory disease of the pelvic region, and other relevant reproductive disorders was gathered using formalized interviewing techniques and through scrutinized documents. The data analysis was done with SPSS v25, calculating p-values in relation to the respondent’s age to determine whether any associations would exist. Results: Menstrual disturbances were frequent, with 30.5% reporting amenorrhea, 25.4% experiencing oligomenorrhea, and 16.9% suffering from menorrhagia. Dysmenorrhea affected 37.3% of participants. Reproductive tract infections were also common; pelvic inflammatory disease was found in 35.6%, vaginal infections in 40.7%, and dyspareunia in 23.7%. No statistically significant association was found between age and any gynecological symptom (p > 0.05). Conclusion: Gynecological issues are highly prevalent in women receiving MDR-TB treatment, regardless of age. These findings highlight the need for integrated reproductive health services within TB management programs to address an often-neglected aspect of patient well-being. Keywords: MDR-TB, Women’s health, Menstrual disorders, Reproductive tract infections, Tuberculosis treatment, Amenorrhea, Pelvic inflammatory disease.